Proceedings of the Third (2016) ACM Conference on Learning @ Scale 2016
DOI: 10.1145/2876034.2876051
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Student Behavior at Scale

Abstract: Understanding why and how students interact with educational videos is essential to further improve the quality of Massive Online Open Courses (MOOCs). In this paper, we look at the complexity of videos to explain two related aspects of student behavior: the dwelling time (how much time students spend watching a video) and the dwelling rate (how much of the video they actually see). Building on a strong tradition of psycholinguistics, we formalize a definition for information complexity in videos. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…To a certain extent, such subjective experiences of interest are characterized by identifiable patterns in reading behavior as well (O'Brien et al, 2020 ). Readers spend more time on interesting sentences than on less interesting sentences (Wade et al, 1993 ), while interest tends to decrease rather than increase reading time at a discourse level (Shirey & Reynolds, 1988 ; van der Sluis et al, 2016 ). Once interested, readers presumably employ their mental resources more effectively and experience fewer distractions (Miller, 2015 ; van der Sluis et al, 2016 ).…”
Section: Background: Eye Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…To a certain extent, such subjective experiences of interest are characterized by identifiable patterns in reading behavior as well (O'Brien et al, 2020 ). Readers spend more time on interesting sentences than on less interesting sentences (Wade et al, 1993 ), while interest tends to decrease rather than increase reading time at a discourse level (Shirey & Reynolds, 1988 ; van der Sluis et al, 2016 ). Once interested, readers presumably employ their mental resources more effectively and experience fewer distractions (Miller, 2015 ; van der Sluis et al, 2016 ).…”
Section: Background: Eye Behaviormentioning
confidence: 99%
“…Readers spend more time on interesting sentences than on less interesting sentences (Wade et al, 1993 ), while interest tends to decrease rather than increase reading time at a discourse level (Shirey & Reynolds, 1988 ; van der Sluis et al, 2016 ). Once interested, readers presumably employ their mental resources more effectively and experience fewer distractions (Miller, 2015 ; van der Sluis et al, 2016 ). These findings suggest that distinctive eye behaviors both precede and follow on the activation of motivational resources typical to the experience of interest (Silvia, 2006 ).…”
Section: Background: Eye Behaviormentioning
confidence: 99%
“…Coursera and Edx) focused on student attrition and the reasons behind that attrition: student preparedness as a function of prior education (Breslow et al, 2013;Kizilcec and Halawa, 2015), student intent (Gasevic et al, 2014) and varied social factors such as structural attributes of students' social networks, lack of social presence or social comparison and the timing of their interactions with fellow students (Davis et al, 2017;Gasevic et al, 2014;Rosé et al, 2014) were among those reasons. This line of research then gave way to an exploration of how students interact with the MOOC from the perspective of how and when they used different types of MOOC resources and features (Pursel et al, 2016;Van der Sluis et al, 2016).…”
Section: Participating By Activity or By Weekmentioning
confidence: 99%
“…That is, shorter and longer videos might differ on a wide variety of other instructional design characteristics which might actually be underlying this correlation. For example, in an analysis of over a hundred MOOC videos it was found that the complexity of the transcript explains almost a quarter of the variance in video dwelling time [47]. Importantly, there is a non-linear relationship, with both low-complex and high-complex videos showing an increased dwelling time.…”
Section: Factors Influencing Students' Video Watching Behaviormentioning
confidence: 99%